Washington View: Money, power, and choices. (November 2018) - Ferguson, Maria
As the 2018 election approaches, education is proving to be a major issue, with dozens of teachers running for office and voters showing strong interest in topics such as school funding and campus safety. However, while voters may be engaged in the issues, they likely have little information about the ways in which big-spending individuals and advocacy groups have influenced their candidates' political platforms .